Design of DOX-GNRs-PNIPAM@PEG-PLA Micelle With Temperature and Light Dual-Function for Potent Melanoma Therapy - Wang, Na; Shi, Jing; Wu, Cong; Chu, Weiwei; Tao, Wanru; Li, Wei; Yuan, Xiaohai (Frontiers in Chemistry, 2021)
Objective: The aim of this study was to construct light and temperature dual-sensitive micellar carriers loaded with doxorubicin (DOX) and gold nanorods (DOX-GNRs-PNIPAM@PEG-PLA, DAPP) for melanoma therapy. Methods: The DAPP self-assembled using fine-tuned physicochemical properties in water. The DAPP structure, temperature- and photo-sensitivity, drug-release, in vitro serum stability, and cytotoxicity against melanoma B16F10 cells were evaluated in detail. The corresponding in vitro and in vivo therapeutic mechanisms were then evaluated using a B16F10-melanoma bearing BALB/c nude mouse model (B16F10). Results: The light and temperature sensitive micellar drug delivery system assembled from block copolymer and gold nanorods exhibited a narrow particle size and size distribution, good biocompatibility, well-designed photo-temperature conversion, controlled drug-release, and high serum stability. Compared with the free DOX- and PBS-treated groups, the cell endocytosis-mediated cytotoxicity and intra-tumor accumulation of DAPP was markedly enhanced by the NIR-light exposure and induced potent in vivo tumor inhibitory activity. Conclusion: The design of DAPP, a dual-functional micellar drug delivery system with temperature- and light-sensitive properties, offers a new strategy for skin-cancer therapy with a potent therapeutic index.